Do initial reserves signal long-term IPO stock performance? - Peng Cheng (Cogent Economics & Finance, 2015)
This research examines the long-run Initial Public Offerings (IPO) stock performance of a large Chinese sample, and in particular the relationship between initial reserves (capital reserves and revenue reserves immediately after the IPO) and long-run IPO stock performance. In general, Chinese IPOs do not underperform the market/industry benchmarks, but they significantly underperform their size-matched industry peers. More importantly, Chinese IPO firms tend to issue a large amount of bonus shares (also called as a ‘capitalization issue’, i.e. capitalization of the reserves) after the IPO. Consistent with bonus share signaling hypothesis, Chinese IPO firms exhibit increased operating/stock performance subsequent to bonus issues. Interestingly, the size of the initial reserves is positively associated with long-run IPO stock performance. This research adds another piece of empirical evidence to the literature whether IPOs underperform in the long run, by confirming that the choice of performance measures and benchmarks could affect the conclusion on the IPO long-run performance. Further, it discovers that size of initial reserves could signal superior IPO stock performance in the long run.